Digital marketing strategy of kampung UMKM, blora district in attracting tourists in the era of pandemi COVID-19 - Izza Ulumuddin Ahmad Asshofi; Ar Ruum Maulanasari; Andi Hallang Lewa (Surya Hijau Manfaat, 2023)
The rapid development of information technology can bring many advantages in various sectors, one of which is the tourism sector. The advantages offered are carried out to develop micro, small and medium enterprises. This research activity aims to determine the impact of the application of digital media on the development of micro, small and medium enterprises to the Blora MSME Village in order to increase sales and attract tourists in the midst of the difficult Covid-19 pandemic by using digital marketing strategies. The role of technology is needed to suppress the success of a business in expanding the market by utilizing information technology that can be used for modern marketing communication media. The advantages offered by digital media range from cost-effective, wide coverage, and easy access to use by the public. therefore, MSME actors who previously only depended on consumers who came, now MSME actors can now market their products on digital media which is considered very profitable. The results of data collection in two ways, namely by literature review and field research, where the authors find that digital media is often used by MSME actors.